Selective serotonin reuptake inhibitors induce cardiac toxicity through dysfunction of mitochondria and sarcomeres - Yawei Shen; Cameron E. Brown; Xiao Li; Peng Zhang; Stacey R. McGee; Søren C. Spina; J. Ricardo Loret de Mola; Joanna L. Fiddler; Haodi Wu; Qing Liu (Communications Biology)
Abstract The administration of selective serotonin reuptake inhibitors (SSRIs) during pregnancy can increase the odds of congenital heart defects in babies. The present study aims to explore the toxic effects of SSRIs on the cardiac systems and the underlying mechanism. We apply human pluripotent stem cells to establish 2D-monolayer cardiomyocyte and 3D-cardiac organoid models to evaluate the effects of three SSRIs (fluoxetine, paroxetine, and sertraline) on cardiac development. We observe that SSRIs exposure inhibited ATP production and mitochondrial respiration and disrupted mitochondrial homeostasis and sarcomere structure in the differentiating cardiomyocytes, presenting high risks of dysfunction and abnormality of cardiomyocytes. Further analyses in the cardiac organoid model show that SSRIs not only reduce mitochondrial respiration and ATP production, but may also affect cardiac development and angiogenesis. Altogether, our study reveals that SSRIs induce mitochondrial dysfunction and sarcomeric disorganization in cardiomyocytes, implying their potential risk to the cardiac system.